Diagnostic tools and CFTR functional assays in cystic fibrosis: utility and availability in Switzerland (Swiss Medical Weekly, 2021)
Cystic fibrosis (CF) is a genetic disease caused by a bi-allelic mutation of the cystic fibrosis transmembrane conductance regulator (CFTR) gene. When the diagnosis cannot be confirmed by a positive sweat test or/and the identification of two CF-causing variants, international guidelines recommend the use of CFTR functional assays. These tests assess whether CFTR activity is normal or diminished/absent through measurement of CFTR-mediated chloride secretion/absorption. CFTR functional assays are not only useful for diagnostic purposes but can also serve as a surrogate outcome for clinical trials of CFTR modulators, which are emerging therapeutic agents designed to correct the malfunctioning protein. In the near future they could also be used as precision-medicine techniques, to help guidance and optimisation of treatment. Until now, sweat testing has been the only CFTR functional assay available in Switzerland. Since 2020, the Centre Hospitalier Universitaire Vaudois (CHUV) at Lausanne and the Lucerne Children’s Hospital perform nasal potential difference measurement. Moreover, The Ecole Polytechnique Fédérale de Lausanne (EPFL) established a reliable procedure to generate adult intestinal organoids, i.e., stem cell-derived in-vitro grown mini tissues, extracted from rectal biopsies, which can be used to assess CFTR function in vitro. This narrative review describes the most popular CFTR functional assays, as well as their indications, limitations and availability in Switzerland.